1970
DOI: 10.3126/kumj.v8i2.3556
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pharmacotherapy in the department of paediatric dentistry

Abstract: Background: Pharmacotherapy plays important role in the management of paediatric dental patients in the department of paediatric dentistry. Many children at their early age suffer from different kinds of dental conditions such as acute and chronic irreversible pulpitis, acute and chronic alveolar abscesses, dentoalveolar and vestibular abscesses, etc along with physiological tooth movement that requires professional help for dental treatment. Treatment of such conditions most frequently requires pharmacotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…This study shows that the entire patient visiting outpatient department of Educare Dental Hospital received the dental therapy. 11 Prescription pattern of the 2802 prescriptions, there were total 5952 drugs used for the treatment of the patients. The majority of the patients attending in the hospital were female (57.6%).…”
Section: Discussionmentioning
confidence: 99%
“…This study shows that the entire patient visiting outpatient department of Educare Dental Hospital received the dental therapy. 11 Prescription pattern of the 2802 prescriptions, there were total 5952 drugs used for the treatment of the patients. The majority of the patients attending in the hospital were female (57.6%).…”
Section: Discussionmentioning
confidence: 99%
“…Similar prescription audit studies in the past have shown that amoxicillin is the most frequently prescribed antimicrobial agent. 1,2,6 Additionally, use of amoxicillin alone or in combination with clavulanate is justifiable as bacteriological epidemiology in odontogenic infections include gram positive facultative anaerobes (68%), gram negative strict anaerobes (30%) and gram positive facultative anaerobes (2%). 13 Moreover, amoxicillin alone or with clavulanate has shown best results in terms of less resistance and more sensitivity than other antimicrobial agents against oral bacterial pathogens.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5] Most commonly prescribed medicines in dentistry are the antimicrobial agents and analgesic agents. 2,6,7 Drug prescription is a dental/medical practitioner's written order to the pharmacist to dispense a medicine or medicines to be administered or taken by the patient in a proper dosage from, dose, frequency and the duration for the treatment. It is an individualized and vibrant clinical process which may be influenced by social, cultural, economic, and/or promotional factors.…”
mentioning
confidence: 99%
“…Ibuprofen was found to dominate over other analgesics [28][29][30][31]. This also applies to pediatric dentistry, whereby ibuprofen and paracetamol predominate in prescription rates [32].…”
Section: Utilization Pattern Of Analgesic Usementioning
confidence: 99%